Minocycline 1-year therapy in multiple-system-atrophy: effect on clinical symptoms and [11C] (R)-PK11195 PET (MEMSA-trial) - Dodel, Richard C.; Spottke, Annika; Gerhard, Alexander; Reuss, Alexander; Reinecker, Sylvia; Schimke, Nicole; Trenkwalder, Claudia; Sixel-Döring, Friederike; Herting, Birgit; Kamm, Christoph; Gasser, Thomas; Sawires, Martin; et al. (Movement disorders, 2010)
The aim of the study was to investigate the efficacy of the antibiotic minocycline as a drug treatment in patients with Multiple-System-Atrophy Parkinson-type (MSA-P). Sixty-three patients were randomized to minocycline 200 mg/d (n = 32) or a matching placebo (n = 31). The primary outcome variable was the change in the value of the motor score of the Unified Multiple-System-Atrophy Rating-Scale (UMSARSII) from baseline to 48 weeks. Secondary outcome variables included subscores and individual Parkinsonian symptoms as determined by the UMSARS and the Unified-Parkinson's-Disease Rating-Scale (UPDRS). Health-related quality of life (HrQoL) was assessed using the EQ-5D and SF-12. “Progression rate” was assumed to be reflected in the change in motor function over 48 weeks. At 24 weeks and 48 weeks of follow-up, there was a significant deterioration in motor scores in both groups, but neither the change in UMSARSII nor in UPDRSIII differed significantly between treatment groups, i.e. “progression rate” was considered to be similar in both treatment arms. HrQoL did not differ among the two treatment arms. In a small subgroup of patients (n = 8; minocycline = 3, placebo = 5)[11C](R)-PK11195-PET was performed. The three patients in the minocycline group had an attenuated mean increase in microglial activation as compared to the placebo group (P = 0.07) and in two of them individually showed decreased [11C](R)-PK11195 binding actually decreased. These preliminary PET-data suggest that minocycline may interfere with microglial activation. The relevance of this observation requires further investigation. This prospective, 48 week, randomized, double-blind, multinational study failed to show a clinical effect of minocycline on symptom severity as assessed by clinical motor function. © 2009 Movement Disorder Society
Published online 11 December 2009
Gesehen am 13.02.2023